If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(36+2x)(48+2x)=0
We add all the numbers together, and all the variables
(2x+36)(2x+48)=0
We multiply parentheses ..
(+4x^2+96x+72x+1728)=0
We get rid of parentheses
4x^2+96x+72x+1728=0
We add all the numbers together, and all the variables
4x^2+168x+1728=0
a = 4; b = 168; c = +1728;
Δ = b2-4ac
Δ = 1682-4·4·1728
Δ = 576
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{576}=24$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(168)-24}{2*4}=\frac{-192}{8} =-24 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(168)+24}{2*4}=\frac{-144}{8} =-18 $
| -2-8x=11+11x | | 3x+188=10x-8 | | 5(2x-1)=3(3x+4 | | 5x+70=7x | | 9-4x=-51+11x | | .-2x+3(1+x)=x+5-2 | | 9x+58=4 | | V/V=p/p | | 16u-10u+u=7 | | 2(3x+1)=2x+4x+1 | | 1/4(t-3)+2=1/3(t+6) | | 2(3x-1=4x+7 | | 4d-3d=8 | | -1(x+2)=13 | | x-9=8(x+3)-18 | | r+10+7r=26 | | 3z/7+3=-7 | | 10g−3g−4g+g−2g=10 | | (4)^x+3=1/16 | | (z+10)^(3/2)=1 | | 13r-11r=20 | | a-1/6=2+1/3 | | -16m=-80 | | .6x+2.7=0.9x | | 2/5=2/3n | | -5x+28=11 | | -1.3j=0.4=-1.16 | | a-1/6=21/3 | | 10y=10+30 | | -4=8y-9y=6 | | x/x-4=4/7 | | 3y-6-2y=5 |